Effectiveness of The Educational Game “Engklek” In Prevention of Dengue Hemorrhagic Fever - Deska Viorentira; Marleni Marleni; Ayudita Ayudita (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito, which can be prevented by implementing the PSN 3M Plus principle, namely draining, covering, recycling, and taking additional measures. This study aims to evaluate the effectiveness of the educational game